Exploring the Use of Seabirds as a Dynamic Ocean Management Tool to Mitigate Anthropogenic Risk to Large Whales - Tammy L. Silva; Kevin D. Powers; Jooke Robbins; Regina Asmutis-Silvia; Timothy V. N. Cole; Alex N. Hill; Laura J. Howes; Charles A. Mayo; Dianna Schulte; Michael A. Thompson; Linda J. Welch; Alexandre N. Zerbini; et al. (Frontiers in Marine Science, 2022)
Vessel strike and entanglement in fishing gear are global threats to large whales. United States management actions to reduce human-induced serious injury and mortality to large whales have been inadequate, partially due to static, spatial protection schemes that fail to adjust to distribution shifts of highly mobile animals. Whale conservation would benefit from dynamic ocean management, but few tools exist to inform dynamic approaches. Seabirds are often found in association with whales and can be tagged at lower cost and in higher numbers than whales. We explored the use of satellite-tagged seabirds (great shearwaters) as dynamic ocean management tools for near real-time identification of habitats where humpback and North Atlantic right whales aggregate, potentially increasing anthropogenic risk. We identified shearwater habitat use areas in the Gulf of Maine with 50% kernel density utilization distributions at yearly, monthly, and weekly scales using satellite-telemetry data from 2013-2018. We quantified overlap using whale sightings and whale satellite telemetry data at two spatial scales: Stellwagen Bank National Marine Sanctuary and the Gulf of Maine. Within the sanctuary, shearwaters overlapped with >50% of humpback sightings in 4 of 6 (67%) years, 15 of 23 (65%) months, and 50 of 89 (56%) of weeks. At the Gulf of Maine scale, shearwater use areas overlapped >50% of humpback sightings in 5 of 6 years (83%) and 16 of 22 (73%) months, and encompassed humpback 50% utilization distributions (based on satellite telemetry) in 2 of 3 (66%) years and 7/12 (58%) months analyzed. Overlap between shearwaters and right whales was much lower, with >50% overlap in only 1 of 6 (17%) years and 3 of 23 (13%) months. These initial results demonstrate that satellite-tagged shearwaters can be indicators of humpback whale habitat use in both space and time. With further study, tagged shearwaters may provide near-real time information necessary to operationalize dynamic management to mitigate human impacts on humpback whales.